A shared oligodendrocyte activation state associated with neuroinflammation and neurodegeneration. (1st February 2022) - Kenigsbuch, Mor; Bost, Pierre; Halevi, Shahar; Yehuda, Hila Ben; Hajbi, Renana; Schwikowski, Benno; Peles, Elior; Amit, Ido; Schwartz, Michal
Abstract: Background: Alzheimer's disease (AD) is a devastating neurodegenerative disease. Despite intensive research, all current therapeutic attempts have failed, highlighting the need for new therapeutic approaches. While most research traditionally attributed cognitive impairment to neuronal damage, recent studies have highlighted the role of non‐neuronal cells, mainly the brain innate‐immune cells, the microglia. However, the contribution of non‐immune glial cells remains elusive.Oligodendrocytes are the central nervous system myelin‐forming cells and are crucial for proper neuronal signaling and brain function. However, little is known about their fate in AD. In our study, we aimed to reveal cellular heterogeneity among non‐immune glia, and particularly oligodendrocytes, in AD. Method: To this end, we used the 5xFAD model of AD and performed single cell RNA‐sequencing, bulk RNA‐sequencing, computational meta‐analysis and immunofluorescence stainings in mouse and human AD brain. Result: We found that oligodendrocytes are the most affected cell type and unveiled a novel oligodendrocyte cell‐state, which we termed 'Disease‐associated OLigodendrocytes' (DOLs). DOLs were found in the AD mouse brains but not in the wild‐type (WT), spatially associated with amyloid‐beta plaques and increased with disease progression. DOL signature points at possible interactions with the immune system and immune‐related signaling, plaque propagation, and blood‐brain‐barrier interference. Meta‐analysis across other neuroinflammatory and neurodegenerative conditions revealed a conserved oligodendrocyte response similar to DOLs. Bulk RNA‐sequencing of oligodendrocytes following different stimulations revealed partial similarity between DOL signature and oligodendrocyte response to specific inflammatory cues. Lastly, we showed that DOLs are present also in human AD brains but not in healthy controls. Conclusion: Overall, this study demonstrates that oligodendrocytes have a common response to neuroinflammation and neurodegeneration, which is recapitulated in humans, and can serve as a potential therapeutic target in multiple pathologies.